Interview with Carolyn Robinowitz, MD - , (MD Conference Express, 2008)
Carolyn Robinowitz, MD, 2007–2008 President of the American Psychiatric Association, took a moment to extend a special greeting to international physicians accessing highlights of the conference through the pages of MD Conference Express®.